Cognitive and Psychological Constructs of Korean Physical Literacy Scale in Children - Inkyoung Park; Jaehyeok Sim; Youngho Kim (The Asian Journal of Kinesiology, 2023)
OBJECTIVES The current study examined the cognitive and psychological factors of Canadian Assessment of Physical Literacy-2 (CAPL-2) using a cross-sectional design. Also, this study assessed the measurement and structural invariance of the CAPL-2. METHODS The survey was conducted on 539 elementary school students in Seoul, Korea. Among the collected data, 274 datasets were used for confirmatory factor analysis, and 25 datasets for test-retest reliability analysis and 240 datasets for differences by group. Confirmatory factor analysis, reliability analysis, and criterion-related validity analysis were carried out by using SPSS 23.0 and AMOS 23.0. RESULTS Results indicated that the Korean physical literacy scale consists of four factors (interest, motivation, competence, and understanding with 15 items). In addition, the findings revealed that all factors in physical literacy differed by the stage of physical activity (λ= .723, F=5.59, p<.001). CONCLUSIONS This study was the first to validate the CAPL-2 into the Korean children. The Korean physical literacy scale offers the possibility of assessing physical literacy to researchers and practitioners and Korean children’s physical activity enhancement could be easily tracked in school and community settings.